Preparation of Kaseesadi Malahara - A Practical Approach (AYUSHDHARA, 2025)
Malahara Kalpana comes under Bahya Kalpana (external application) is a ointment preparation. The primary base of Malahara Kalpana is Siktha, Taila (bees wax and oil) and other ingredients based on intended use can include herbal, minerals may be added is called Malahara so because it removes Mala (residue etc) from Vrana, Vidhradi, Twakvikara etc conditions and offers benefits like Snehana (oleation), Shodhana (purification) and Ropana (healing), Lekhana (scraping), based on ingredients provides range of utility. Materials and Methods: Kaseesadi Malahara is the preparation consisting of Shudha Kaseesa, Saindhava Lavana, Kinva, Haridra, Daruharidra, Vacha, Tila taila, Sikta. considered to be beneficial in Dusta Vrana, Kaseesadi Malahara is explained in Susrutha Samhita is herbomineral formulation. It was prepared as per classical reference. Observation and Results: method of preparation was documented the yield of Malahara was 7kgs and was yellow in color which was preserved in air tight container. Discussion and Conclusion: there is wide range of description available about Malahara in authoritative classics. This ointment preparation has many therapeutic usages and is effective in treating many disorders, it is intended to be used externally simple formulation indicated in Dusta Vrana, which is economical. The paper details the most practical way of preparing Kaseesadi Malahara for clinical use.